2010
DOI: 10.1039/c0cc01098g
|View full text |Cite
|
Sign up to set email alerts
|

Polyoxometalate assisted photoreduction of graphene oxide and its nanocomposite formation

Abstract: We have developed a green method to reduce graphene oxide via a UV-irradiated photoreduction process in which H(3)PW(12)O(40) was used as photocatalyst. Moreover, H(3)PW(12)O(40) can adsorb on the reduced graphene oxide as anionic stabilizer and lead to water dispersible graphene sheets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
146
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(153 citation statements)
references
References 39 publications
6
146
1
Order By: Relevance
“…[17][18][19]23,25,26,30,35,37,[52][53][54][55][56][57][58][59] These plenary POMs can be reduced by multiple electrons while maintaining their structural integrity and act as cathodes to efficiently transfer electrons to the organic material or metal.…”
Section: (α2) Via Uv Irradiationmentioning
confidence: 99%
See 1 more Smart Citation
“…[17][18][19]23,25,26,30,35,37,[52][53][54][55][56][57][58][59] These plenary POMs can be reduced by multiple electrons while maintaining their structural integrity and act as cathodes to efficiently transfer electrons to the organic material or metal.…”
Section: (α2) Via Uv Irradiationmentioning
confidence: 99%
“…[17][18][19][37][38][39]57,58 Here we employ photoactivation of the lacunary α2 for reduction of TcO 4 -and ReO 4 -, and complexation of the reduced metal into the defect binding site. The α2 accepts 2 electrons from a sacrificial electron donor and transfers these electrons to TcO 4 -for reduction to Tc V quantitatively in a "one-pot" reaction.…”
Section: (α2) Via Uv Irradiationmentioning
confidence: 99%
“…An additional obstacle that presents itself when chemically reduced graphene oxide (rGO) is produced is the poor quality of the process. This is because the rGO tends to form irreversible aggregations, which result from strong van der Waals attractive forces between the graphene planes, unless a modification step (both covalent and non-covalent) is included in the process (44,45,46). Recently, efforts have been made toward addressing the above-mentioned problems by using natural products instead of toxic-reducing agents.…”
Section: Introductionmentioning
confidence: 99%
“…They observed over an order of magnitude increase in conductivity after the reduction of graphene oxide TiO 2 suspension. Another facile method was reported by Li et al by using polyoxometalate as a catalyst [3]. This method was used by Zhang et al for inkjet printing of multi-layer films, which were demonstrated to be excellent chemical sensors [4].…”
mentioning
confidence: 99%